2017
DOI: 10.1007/s11661-017-4199-2
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Strain Gradient and Anisotropy in Gradient-Structured Metal

Abstract: Gradient-structured metals have been reported to possess superior mechanical properties, which were attributed to their mechanical heterogeneity. Here we report in-situ observation of the evolution of strain gradient and anisotropy during tensile testing of a gradient-structured metal. Strain gradients and anisotropy in the lateral directions were observed to increase with increasing applied tensile strain. In addition, the equivalent Poisson's ratio showed gradient, which evolved with applied strain. The grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 45 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…This reversal signals a redirection of lateral compressive stress, instead of a decrease in magnitude of ε 22 [41]. It is the result of inter-layer interaction due to the e-p incompatibility by the difference in apparent Poisson's ratio between the plastically deformed CG layer (ν=0.5) and still elastic NS layer [6,[42][43][44]. The second is load partitioning, an inevitable result of the change of stress state.…”
Section: Layer-by-layer Yieldingmentioning
confidence: 99%
“…This reversal signals a redirection of lateral compressive stress, instead of a decrease in magnitude of ε 22 [41]. It is the result of inter-layer interaction due to the e-p incompatibility by the difference in apparent Poisson's ratio between the plastically deformed CG layer (ν=0.5) and still elastic NS layer [6,[42][43][44]. The second is load partitioning, an inevitable result of the change of stress state.…”
Section: Layer-by-layer Yieldingmentioning
confidence: 99%
“…The facet size for the strain calculation using DIC method was 50 μm. The other details for the DIC method can be found in our recent paper 48 .…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Moreover, we reported an "in-situ" evolution of the induced strain gradients in a gradient-structured metals during uniaxial tension [57]. We found that the lateral strain gradients increase with increasing applied tensile strain, and the strain gradients increase faster and the back-stress hardening plays more important role at the elasto-plastic transition stage.…”
Section: Tensile Behaviors Of Gradient Grained Structuresmentioning
confidence: 90%